2020
DOI: 10.1084/jem.20192312
|View full text |Cite
|
Sign up to set email alerts
|

The omentum, a niche for premetastatic ovarian cancer

Abstract: The work by Etzerodt et al. in this issue of JEM (https://doi.org/10.1084/jem.20191869) identifies a distinct omentum-resident macrophage population of embryonic origin and demonstrates that these cells provide a niche for ovarian cancer metastasis and cancer stemness. This research opens up for many questions and therapeutic prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…Soft tissue thickening, nodularity, and all are the signs of peritoneal involvement [6]. The tumor cells traverse the peritoneum through the "transcoelomic" spread with the omentum being the most common site of these metastases [7].…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue thickening, nodularity, and all are the signs of peritoneal involvement [6]. The tumor cells traverse the peritoneum through the "transcoelomic" spread with the omentum being the most common site of these metastases [7].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer associated fibroblasts (CAFs) promote tumorigenesis through production of cytokines, growth factors, and extracellular matrix components, leading to worsening fibrosis and tumor growth [ 8 ]. Subsequent to the growth of cancer cells in the ovary, these cells are susceptible to spread within the peritoneal cavity, homing to the highly vascular, fatty tissue of the omentum that uses immunologic and metabolic mechanisms to promote tumor growth [ 9 ]. In order to understand the role of HE4/ WFDC2 in ovarian cancer, it is important to consider its known functions and how these might interplay with this complex ovarian tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the omentum is involved in the immune response and fluid exchange of the human abdominal cavity [ 4 ]. In addition, it is becoming increasingly apparent that the omentum is directly involved in the development of a series of cancers, including ovarian cancer, gastric cancer, and pancreatic cancer [ 5 , 6 , 7 ]. Previous research has suggested that adipocytes provide energy for the rapid growth of ovarian cancer and enhance tumor cell metastasis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%